3D modelling and x-ray depth analysis map of the pulp with computer software via digital periapical radiography and cone beam computed tomography. - Felek, Turgut; Satir, Samed; Ozel, Selale; Celik, H. Kursat (BMC Oral Health, 2025)
Objective: Periapical radiographs (PAR) offer information about the pulp and periodontal health of teeth. However, intraoral radiographs are insufficient for diagnosing buccolingual anomalies and variations such as bifid canals due to their two-dimensional nature. Cone beam computed tomography (CBCT) is the gold standard for 3D imaging in the clinic but requires additional radiation. The aim of this study was to create a software (XPAR) which obtains x-ray depth analysis and 3D modelling of the pulps of single-rooted teeth by converting the grey values in the original radiographs into numerical data. Materials and methods: Two single-rooted teeth were included in the experimental part of the study. Chicken fibula bone was preferred for alveolar bone simulation because it could simulate cortical and trabecular structures due to similarity. A total of four images (60kVp & 70kVp; single alveolar bone & double alveolar bone) were obtained. The aim of this experimental part is to test the repeatability and realism of the algorithm to be created for pulp modelling. Retrospectively, 31 single-rooted teeth with both periapical radiography and cone-beam computed tomography imaging were included in the retrospective part of the study. According to XPAR, depth increase areas were interpreted as root resorption and accessory canal. Depth decrease areas were evaluated as the transformation of the pulp from an elliptical to an oval form, pulp stone, bifid canal formation and the presence of thick alveolar bone. The diagnostic accuracy of XPAR application on pathological and morphological changes was evaluated by comparing the obtained results with CBCT. Results: 80% of the analyses diagnosed as bifurcation by XPAR application were supported by CBCT. This rate decreased to 27% in the diagnosis of transitions from elliptical to oval form. A total of 5 and 19 linear formations observed in the form of depth decrease and increase, respectively, were accepted as image errors in XPAR. Conclusion: Buccolingual bifid canal formations and pulp obliterations can be diagnosed with a rate of nearly 50% with the depth decrease finding obtained in XPAR application. Imaging errors caused by deformed detectors are typically observed as linear formations. Highlights: A software named XPAR was studied to perform x-ray depth analysis and 3D pulp modelling from radiographs. XPAR software converts radiograph grey values into numerical data for 3D modelling. Study tested two single-rooted teeth using chicken fibula for alveolar bone simulation. XPAR showed 80% accuracy for bifurcation diagnosis compared to CBCT results. XPAR diagnoses bifid canals and pulp obliterations with ∼ 50% accuracy; some image errors.